The Impact of ESG Ratings on Financial Performance of the Companies: Evidence from BRICS Countries - StrekalinaAnastasia; ZakirovaRenata; ShinkarenkoAlena; VatsaniukEvgenii (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2023)
Non-financial factors become the relevant topic in the context of understanding the successful development of companies over the world. The purpose of this paper is to study the relationship between ESG scores and financial performance of firms operating in emerging markets, in particular BRICS countries. This study includes three financial performance indicators to cover three different perspectives: accounting measure (ROA), market performance (TSR) and economic metric (EVA spread). The ESG scores, its pillars and other financial metrics are taken from Refinitiv Eikon. The sample consists of 257 listed companies operating in BRICS countries throughout 2017–2021. The main method of the research is the Fixed Effect method for panel data. The results showed that there is no statistical significance between ESG and ROA. Besides, government pillars negatively affect ROA through CSR that is explained by legitimacy theory. As for TSR, ESG, social and environment pillars have positive effects on market performance measure, following stakeholder theory. Regarding economic performance, ESG and social pillar have negative influence on EVA spread.